Odontologi Forensik Sebagai Metode Identifikasi dan Alat Bukti di Pengadilan - Ramadhani, Ginanda Mutiara; Adriano; Chomariyah (Magister Ilmu Hukum - Universitas Hang Tuah, 2023)
Disasters that have occurred in recent years have resulted in many deaths. Health Law No. 36 of 2009 gives the government and the general public authority for identifying bodies. DNA, fingerprinting, and odontology procedures provide the highest levels of individual validity among victim identification approaches. Odontological identity in medical records, primarily through odontograms, can offer a new perspective as a reference in making forensic reports as evidence in legal proceedings. This research is normative juridical research with three approach methods used, namely the statutory approach, conceptual approach, and comparative approach. The new Health Law supports the Minister of Health's regulation and states that health service units must digitize medical records and promote interoperability in medical record history. This aims to provide antemortem data needed for forensic odontology methods if a crime or accident occurs to an individual. Forensic odontology is a very effective method for identifying victims; speed and accuracy are essential in proving the victim's identity and become one of the most vital pieces of evidence in court based on the Criminal Procedure Code, which applies as one of the references for making a post mortem et repertum at the request of an authorized forensic doctor.